Proposed Implementation of Activity-Based Costing in A Manufacturing Company - Lalmi , Aicha; Oudina , Abdelkhalek (Finance and Business Economies Review, 2023)
This article proposes an application of the ABC method in a production company using the traditional method. We compared full costing using the traditional method with this alternative method. The impact of applying the ABC method was in the treatment of indirect costs. The total amount of indirect costs did not change, but the change was in their allocation to products according to the event giving rise to the indirect costs. This method does not penalize the product that consumes more labour units. The application of this method is not immune to certain limitations. These complicate its use in reality, when companies have complex activities.